Student Disengagement in Finnish Comprehensive Schooling - af Ursin Piia; Tikkanen Jenni; Järvinen Tero (Springer, 2025)
There is a clear consensus amongst educational researchers that school engagement contributes to students’ academic development. However, not all students share the enjoyment of learning and a sense of belonging at school, nor are all of them willing to exert effort in learning and school activities. Students who disengage from school are at risk of a range of adverse academic and social outcomes, which, at worst, culminate in students’ decisions to leave school early. Since the beginning of the 1970s, various findings about Finnish students’ school engagement have raised concerns along with the question of why Finnish students repeatedly rank lowly in international comparisons of happiness at school. This chapter provides insights into the issue of Finnish student (dis)engagement from school drawing on a range of research and survey data. In our view, student disen-gagement is a process that develops through an interplay between individual and contextual factors in a vicious circle of negative emotional and cognitive school and learning experiences, and is—if not reversed—rather stable or progressive. For this reason, it is crucial to identify early signs of disengagement and individual, social, and institutional factors associated with it.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling